Pengaruh Keputusan Investasi, Keputusan Pendanaan, dan Kebijakan Dividen Terhadap Nilai Perusahaan - Ardatiya, Elista; Kalsum, Ummi; Kosim, Belliwati (https://jurnal.binamandiri.ac.id/, 2022)
The purpose of this study is to determine the effect of investment decisions, funding decisions, and dividend policies together on firm value in manufacturing companies and to determine the effect of investment decisions, funding decisions, and dividend policies partially on firm value in manufacturing companies. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The sample used is twenty companies. This study uses multiple linear regression analysis techniques. The results show that investment decisions, funding decisions, and dividend policies simultaneously have a significant effect on firm value. Investment decisions has a partially significant effect on firm value, as well as funding decision variables and dividend policy which also has partially significant effect on firm value.